2005
DOI: 10.1111/j.1472-765x.2005.01684.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and colonization properties of Lactobacillus rhamnosus TB1, a broiler chicken isolate

Abstract: T . B O U Z A I N E , R . D . D A U P H I N , P H . T H O N A R T , M . C . U R D A C I A N D M . H A M D I . 2005.Aims: Selected lactic acid bacteria (LAB) isolated from intestinal tract of chicken have been studied in order to investigate their ability to adhere in vitro to Basement Membrane Matrigel (BMM). A selected strain showing a good adherence in BMM test was used for in vivo colonization assays. Methods and Results: In vitro assessment of adhesion of broiler chicken isolates was performed using BMM as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
1
17
0
2
Order By: Relevance
“…A further report by Bouzaineet al (2005) reveals that at 2 to 4 days post hatch, Streptococci and Enterobacteria colonize the small intestine and caecum. The isolation of Bacillus and Streptococcus and species of bacteria from the ileum and caecum of broiler chicken fed BRCM meal in this study corroborates the earlier reports (Cummings andMacfarlane, 1997 andBouzaine, et al, 2005).…”
Section: Microbiological Assaysupporting
confidence: 82%
See 1 more Smart Citation
“…A further report by Bouzaineet al (2005) reveals that at 2 to 4 days post hatch, Streptococci and Enterobacteria colonize the small intestine and caecum. The isolation of Bacillus and Streptococcus and species of bacteria from the ileum and caecum of broiler chicken fed BRCM meal in this study corroborates the earlier reports (Cummings andMacfarlane, 1997 andBouzaine, et al, 2005).…”
Section: Microbiological Assaysupporting
confidence: 82%
“…For example, Mead (1989) reported that the major species present in the small intestines of young chicks was lactobacillus with bifidiobacteria populations becoming more dominant in the caeca at older age. Bouzaine et al (2005) also reported that after the first week, lactobacillus predominates in the small intestine. A further report by Bouzaineet al (2005) reveals that at 2 to 4 days post hatch, Streptococci and Enterobacteria colonize the small intestine and caecum.…”
Section: Microbiological Assaymentioning
confidence: 99%
“…While several articles have described Lactobacillus strains which are able to survive and persist within the GIT of poultry (8,16,31,42,46), the persistence ranged from 1 day through 4 weeks after cessation of administration. Ehrmann et al (16) described the persistence of their two selected strains within ducks for up to 28 days using only a single dose.…”
Section: Discussionmentioning
confidence: 99%
“…Several probiotic bacteria including bifidobacteria and lactobacilli adhere to mucosal tissue in a strain-specific manner (O'Hara & Shanahan, 2007). Selected probiotic strains should be able to compete with pathogens for the same receptors and to occupy their potential binding sites in the gut, thus representing a potential therapeutic strategy (Bouzaine et al, 2005;O'Hara & Shanahan, 2007). This enhances the intestinal persistence of the probiotic bacteria, and limits pathogen access to the epithelium (O'Hara & Shanahan, 2007).…”
Section: Discussionmentioning
confidence: 99%